Revisit Closed-End Fund Puzzles via Dynamic Capital Mobility - Song, Garrison Hongyu; Jain, Ajeet (International Journal of Economics and Financial Issues, 2021)
A theoretic model based on the concepts of constrained arbitrage and capital mobility is proposed to interpret closed-end fund puzzles. Although a discount for a closed-end fund's price relative to its net asset value (NAV) is more prevalent, our model never excludes the possibility of a premium, which depends on the relative magnitude of the key parameters for the closed-end fund and its component stocks. Since closed-end funds tend to be more owned by individual investors who are less likely to be active traders due to investor inertia, and investor enthusiasm is usually higher for stocks than for closed-end funds, the aggregated price of component stocks will be more likely higher than the price of the closed-end fund, thus leading to the discount. Our model further shows that a closed-end fund's discount is negatively related to its expected dividends and the interest rate. The above results are reproduced by simulation. Keywords: Closed-End Fund Puzzles, Constrained Arbitrage, Capital Mobility, Investor Inertia, Investor Sentiment JEL Classifications: G12, G14, G23, G40 DOI: https://doi.org/10.32479/ijefi.11373